CITIZEN’S POLITICAL DISTRUST: THE ROLE OF GROWING MISINFORMATION - Asha, Ikenna Izuchukwu (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Political distrust is a global phenomenon that substantially burdens democratic governance, instigates political, ethnic, social, and personal division, and exposes a nation to underdevelopment. The trend is perversive across the world. While researchers have identified multiple reasons for political distrust, the role of misinformation in political distrust has not received much literature attention. The present study examines citizens' political distrust based on the growing misinformation in contemporary society. Five hundred and twenty-eight youths (n=528) were conveniently selected from different locations in the Enugu States as the respondents. Data for the survey was collected using a self-report measure assessing political distrust and misinformation. Linear regression analysis was conducted on the data, and the result showed that misinformation statistically significantly predicted citizens' political distrust. The study concludes that misinformation is a significant contributory factor in political distrust among the citizens of Nigeria.